Anti-Periodontopathogenic Ability of Mangrove Leaves (Aegiceras corniculatum) Ethanol Extract: In silico and in vitro study - Nugraha, Alexander Patera; Sibero, Mada Triandala; Nugraha, Albertus Putera; Puspitaningrum, Martining Shoffa; Rizqianti, Yuniar; Rahmadhani, Desintya; Kharisma, Viol Dhea; Ramadhani, Nastiti Faradilla; Ridwan, Rini Devijanti; Noor, Tengku Natasha Eleena binti Tengku Ahmad; Ernawati, Diah Savitri (European Journal of Dentistry, 2022)
Objective Mangrove (Aegiceras corniculatum) is an abundant natural marine resource of Indonesia, which can be explored for treating periodontal disease due to its potential as immunoregulatory, antibacterial, and antioxidant properties. The objective of this study was to investigate the active compound from Indonesian mangrove leaf extract (A. corniculatum) (MLE) for developing a herbal-based mouthwash through in silico and in vitro studies.Materials and Methods Phytochemistry and liquid chromatography-high resolution mass spectrometry (LC-HRMS) were done to explore the active compounds in MLE. Chemistry screening and interaction, absorption, distribution, metabolism, and excretion (ADME), molecular docking simulation, and visualization of MLE active compounds as anti-inflammatory, antioxidant, and antibacterial were investigated in silico The inhibition zone of MLE against Aggregatibacter actinomycetemcomitans (Aa), Porphyromonas gingivalis (Pg), and Fusobacterium nucleatum (Fn) as periodontopathogenic bacterias was performed by diffusion method. Doxycycline 100 mg was used as a positive control, as a treatment group, there were five groups, namely 0%, 25%, 50%, 75%, and 100% MLE.Results Alkaloid, saponin, flavonoid, triterpenoid, steroid, tannin, and quinone were detected in MLE. A high concentration of (-)epicatechin and coumaric acid (CA) were found in MLE. MLE in 100% concentration has the most effective ability to inhibit Fn, Pg, Aa growth in vitro. (-)-Epicatechin has a higher negative binding affinity than CA that can enhance heat shock protein (HSP)-30, HSP-70, HSP-90, interleukin-10, and FOXP3 and also inhibit interleukin-6, peptidoglycan, flagellin, and dectin in silico.Conclusion MLE of A. corniculatum has antioxidant, anti-inflammatory, and antibacterial activities that can be a potential raw material for developing a herbal-based mouthwash.
Keywords: mangrove leaf extract; human health; good health and well-being; medicine; dentistry